ALFONSO PECHA'S TREATISE ON THE ORIGINS OF THE GREAT SCHISM: WHAT AN INSIDER "SAW AND HEARD". (21st November 2017) - LERNER, ROBERT E.
Abstract : The Conscriptio of Alfonso Pecha that treats the origins of the Great Schism of the West has not attracted the attention it deserves. Alfonso Pecha was the confessor and trusted familiar of Cardinal Pedro de Luna at the time of the outbreak of the Schism and was well located to be minutely informed of events surrounding the fateful conclave of April 1378. Hence his detailed narrative, albeit explicitly written to promote the cause of Urban VI, is a very valuable source. Aside from recounting numerous lively conversations and depicting vivid scenes, it contains a report of a hitherto unknown mission in the summer of 1378 to King Charles V of France that probably resulted in emboldening the cardinals to break unanimously with Urban in a new election. Moreover, the Schism narrative constitutes only one of three parts of Alfonso's Conscriptio : the other two seek to prove Urban VI's legitimacy by means of supernatural visions and confirmations from canon law. By the analysis of diverse evidence the conclusion is reached that Alfonso Pecha composed the Conscriptio in Genoa in 1386. The work was published by Franz Bliemetzrieder in 1909 on the basis of a single manuscript located in Basel. The present study with appended edition draws on a second complete manuscript copy located in Prague, particularly important for revealing the identity of the dedicatee, a councilor of Giangaleazzo Visconti. It also draws on a small portion of the text from a manuscript in Uppsala.